2018
DOI: 10.1038/s41598-018-19957-z
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis patient antibodies highly recognize IL-2 in the immune response pathway involving IRF5 and EBV antigens

Abstract: Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by a progressive joint damage due to largely unknown environmental factors acting in concert with risk alleles conferring genetic susceptibility. A major role has been attributed to viral infections that include past contacts with Epstein-Barr virus (EBV) and, more recently, to non-protein coding sequences of human endogenous retrovirus K (HERV-K) integrated in the human genome. Molecular mimicry between viral and self proteins is supposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 32 publications
5
27
0
Order By: Relevance
“…MAP and EBV infections can lead to the deregulation of the Interferon regulatory factor 5 (IRF5) pathway. The frequency of Abs reactivity against IRF5 was increased in RA patients compared to healthy controls (56% vs. 9%, p < 0.0001) [ 59 ]. A similar trend was found for Abs against the EBV tegument protein called BOLF1, where the frequency of reactivity was 44% vs. 9% ( p < 0.0001), in RA patients and healthy controls, respectively [ 59 ].…”
Section: Ra Immunopathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…MAP and EBV infections can lead to the deregulation of the Interferon regulatory factor 5 (IRF5) pathway. The frequency of Abs reactivity against IRF5 was increased in RA patients compared to healthy controls (56% vs. 9%, p < 0.0001) [ 59 ]. A similar trend was found for Abs against the EBV tegument protein called BOLF1, where the frequency of reactivity was 44% vs. 9% ( p < 0.0001), in RA patients and healthy controls, respectively [ 59 ].…”
Section: Ra Immunopathogenesismentioning
confidence: 99%
“…The frequency of Abs reactivity against IRF5 was increased in RA patients compared to healthy controls (56% vs. 9%, p < 0.0001) [ 59 ]. A similar trend was found for Abs against the EBV tegument protein called BOLF1, where the frequency of reactivity was 44% vs. 9% ( p < 0.0001), in RA patients and healthy controls, respectively [ 59 ]. Finally, it was found that Abs against MAP_4027 have a higher reactivity in RA patients compared to the control group (21% vs. 9%, p < 0.0076) [ 59 ].…”
Section: Ra Immunopathogenesismentioning
confidence: 99%
“…paratuberculosis (MAP), that is responsible for important economic losses due to reduced milk production, premature culling, reduced slaughter value and continued spread of infection [1,2]. Furthermore, MAP has a clear zoonotic potential since it has been postulated as a possible trigger factor in several autoimmune diseases in humans such as Crohn's disease (CD) [3,4], type I diabetes (T1D) [5], multiple sclerosis (MS) [6,7] or rheumatoid arthritis (RA) [8,9]. One mechanism that has been suggested to cause the onset and/or exacerbation of autoimmune disease is molecular mimicry, whereby MAP antigens share sequences or structural similarities with self-antigens [10], so the immune response against MAP antigens could also induced undesirable immune responses against host proteins in genetically predisposed individuals [11].…”
Section: Introductionmentioning
confidence: 99%
“…The low level of IL‐2 and the absence of IL‐2 signal in RA patients lead to the development and dysfunction of regulatory T cells, the weakening of immunosuppressive function of autoreactive T cells, the breakdown of immune tolerance and homeostasis of internal environment and the occurrence of autoimmune inflammation . The latest study found that anti‐IL‐2 antibodies exist in RA patients, which can destroy T cell immune balance . Low dose of IL‐2 can promote the proliferation of regulatory T cells, inhibit the role and function of Thl7 cells and help control inflammation‐mediated joint damage .…”
Section: Low‐dose Il‐2 In the Treatment Of Rheumatic Immune Diseasesmentioning
confidence: 99%
“…63 The latest study found that anti-IL-2 antibodies exist in RA patients, which can destroy T cell immune balance. 75 Low dose of IL-2 can promote the proliferation of regulatory T cells, inhibit the role and function of Thl7 cells and help control inflammation-mediated joint damage. 46 Kosmaczewska et al separated PBMCs from RA patients and stimulated them with recombinant IL-2 in vitro.…”
Section: Low Dose Of Il-2 In the Treatment Of Ramentioning
confidence: 99%